Enola Holmes : the Case of the Missing Marquess [Prípad zmiznutého markíza anglicky]. [Book 1] - Springer, Nancy, 1948- (HOT KEY BOOKS, 2020)
Meet Enola Holmes, teenaged girl turned detective and the younger sister to Sherlock Holmes.When Enola discovers her mother has disappeared, she quickly embarks on a journey to London in search of her. But nothing can prepare her for what awaits. Because when she arrives, she finds herself involved in the kidnapping of a young marquess, fleeing murderous villains, and trying to elude her shrewd older brothers-all while attempting to piece together clues to her mother's strange disappearance. Amid all the mayhem, will Enola be able to decode the necessary clues and find her mother?